DEVELOPMENT AND CURRENT PROBLEMS OF TRANSPORT SERVICES AND LOGISTICS SERVICES (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the role of transport services and logistics services in the development of the economy, their mutual integration, digitalization, and ensuring competitiveness in the international market. Also, the current state and promising directions for the development of logistics infrastructure in Uzbekistan are considered.